Combination of Mangosteen (Garcinia mangostana L.) Pericarp Extract and Physical Exercise Decreases Atherosclerotic Lesions in Atherogenic Diet-Fed Rats - Andreas Arie Setiawan; . Sugiri; Awal Prasetyo; Eirin Yovita Kurniawan; Dominikus Evano Putra (Traditional and Integrative Medicine)
The mangosteen pericarp (MP) has xanthone compounds, particularly alpha-mangostin (α-MG), which have been shown to exhibit potent antioxidant and anti-inflammatory activities. Physical exercise (PE) has also been shown to have atheroprotective effects. To date, their combined effect on atherosclerosis has not been studied histologically. This study aimed to investigate the effect of MP extract combined with PE on atherosclerotic changes in rats fed an atherogenic diet. Twenty-five male Wistar rats (Rattus norvegicus) aged 6-8 weeks were randomly divided into five groups of five rats each: C (control, normal diet), CH (atherogenic diet), T1 (atherogenic diet plus MP extract 800 mg/kg/day in three divided doses with PE), T2 (atherogenic diet plus MP extract-loaded nanoemulsion 50 mg/kg/day with PE), and T3 (atherogenic diet plus atorvastatin 1.44 mg/day with PE). The PE protocol involved daily treadmill running for 60 min at 12 m/min, 5 days/week. All rats were treated for eight weeks. Following eight weeks of treatment, the animals were sacrificed and the aortic tissues were taken for histological study. The histological features in groups CH, T1, T2, and T3 were consistent with type Vc atherosclerotic lesion (fibrotic lesion) with intimal thicknesses of 11.99 ± 0.88 μm, 3.61 ± 0.53 μm, 3.48 ± 0.47 μm, and 2.96 ± 0.20 μm, respectively. A comparative analysis revealed a significant reduction in intimal thickness in groups T1, T2, and T3 compared to the CH group (p <0.001). Group T2 exhibited a non-significant decrease compared to group T1 (p = 0.691). Moreover, neither the T1 nor T2 groups significantly differed from the T3 group (p = 0.052 and 0.128, respectively). In conclusion, the combination of MP extract (and its nanoemulsion) and PE decreases atherosclerotic lesions and provides comparable results to the atorvastatin-treated group, indicating their potential as alternative options for preventing atherosclerosis.